Experience of using tacrolimus as a part of a complex therapy of atopic dermatitis - N. N. Filimonkova; Y. V. Kascheeva; M. S. Kolbina (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
This review presents the results of international and Russian clinical studies conducted to assess the efficacy and safety of topical calcineurin inhibitors (TCIs) for the treatment of atopic dermatitis. The main mechanisms of action of TCIs are described. The authors demonstrate the advantages of Tacrolimus belonging to the TCI group. Due to the hydrophilic drug form and pharmacoeconomic index promoting compliance with treatment, it is possible to consider the new drug Tacropic (0.1% and 0.03% Tacrolimus ointments) as the optimum topical drug for the treatment of moderate to severe and severe forms of atopic dermatitis in adults and children.